Floods and firms: Vulnerabilities and resilience to natural disasters in Europe - Fatica, Serena; Kátay, Gábor; Rancan, Michela (Journal of Financial Stability, 2026)
Combining a rich database on natural hazards, granular flood hazard maps and detailed information on firm geolocalization, we study the dynamic effects of floods on European manufacturing firms over the period 2007-2018. We find that water damages significantly and persistently worsen firms’ performance, and may endanger their survival. An average flood deteriorates total assets by about 2% in the year after the event, and up to 5% seven years out. Repeated flooding has milder impacts, suggesting that adaptation measures are adopted in flood-prone areas. We show how reallocation of economic activity within flooded regions can reconcile our results with the “creative destruction” hypothesis for natural disasters.